Water chemistry of nuclear reactor systems proceedings of an international conference organized by the British Nuclear Energy Society, Bournemouth, 24-27 October 1977. (British Nuclear Energy Society, 1978)
Proceedings of an international conference held in Bournemouth on 24-27 October 1977.